Slope Improvement using Combination of Coconut Husks, Coconut Flakes, Luffa, Pineapple Leaves and Vege-Grout - Omar et al., Rohayu Che (International Journal of Advanced Science and Technology, 2019)
The principle of sustainability is about maintaining and improving environmental, social and economic resources to meet the needs of current and future generations. The application of geotextile and micro-bacteria from agricultural waste as Vege-Grout-COLUFNAS, as geotextile and soil induced is therefore implemented as an option for soil treatment/slope improvement.  Application of Vege-Grout-COLUFNAS at the experimental site has shown that natural geotextiles have an important impact on managing ground erosion based on the site observation and measurement shows the reducing of the weight of soil reduced by 70 %.   These researches have shown that the mixed implementation of Vege-Grout-COLUFNAS indicates an increase in safety factor (FOS) from 1,192 to 1,958.  It demonstrates that the Vege-Gout-COLUFNAS type J seam was used as tensile reinforcement to stabilize the slope and also acts as a filter that prevents internal erosion within the slope.